Firefly luciferase: an adenylate-forming enzyme for multicatalytic functions. - Inouye, S. (Cellular and molecular life sciences. CMLS, 2010)
Firefly luciferase is a member of the acyl-adenylate/thioester-forming superfamily of enzymes and catalyzes the oxidation of firefly luciferin with molecular oxygen to emit light. Knowledge of the luminescence mechanism catalyzed by firefly luciferase has been gathered, leading to the discovery of a novel catalytic function of luciferase. Recently, we demonstrated that firefly luciferase has a catalytic function of fatty acyl-CoA synthesis from fatty acids in the presence of ATP, Mg(2+) and coenzyme A. Based on identification of fatty acyl-CoA genes in firefly, Drosophila, and non-luminous click beetles, we then proposed that the evolutionary origin of firefly luciferase is a fatty acyl-CoA synthetase in insects. Further, we succeeded in converting the fatty acyl-CoA synthetase of non-luminous insects into functional luciferase showing luminescence activity by site-directed mutagenesis.